2017
DOI: 10.1049/iet-nbt.2016.0223
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of metal nanoparticles loaded ultrasonic‐assisted Spirulina platensis using algal extract and their antimicrobial activity

Abstract: The synthesis of metal nanoparticles (NPs) loaded on the ultrasonic-assisted Spirulina platensis (MNPs/UASP) was investigated using the green synthesis method. The S. platensis algal extract was taken as a reducing agent. The formations of metal NPs were characterised using UV-visible spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The antimicrobial activity of different metal NPs demonstrated various inhibitory activities against one gram-positive bacteria (Staphylocicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The average size of the particles was calculated using Debye-Scherrer"s formula. green synthesised metal nanoparticles loaded ultrasonicassisted S. platensis algal extract showed rougher and irregular spores developed on the surface of UASP and confirmed that the metal nanoparticles (Ag, Cr, Pb and Zn) were successfully coated on UASP material (Gunasundari et al, 2017) [9] . In line with this result of Santhosh Kumar et al (2014) [10] revealed that SEM images of Psidium guajava mediated TiO 2 NPs were smooth and sphericalin shape with various physical morphology, particle size and aspect ratio.…”
Section: Results and Discussion Uv-vis Absorbance Spectroscopymentioning
confidence: 69%
“…The average size of the particles was calculated using Debye-Scherrer"s formula. green synthesised metal nanoparticles loaded ultrasonicassisted S. platensis algal extract showed rougher and irregular spores developed on the surface of UASP and confirmed that the metal nanoparticles (Ag, Cr, Pb and Zn) were successfully coated on UASP material (Gunasundari et al, 2017) [9] . In line with this result of Santhosh Kumar et al (2014) [10] revealed that SEM images of Psidium guajava mediated TiO 2 NPs were smooth and sphericalin shape with various physical morphology, particle size and aspect ratio.…”
Section: Results and Discussion Uv-vis Absorbance Spectroscopymentioning
confidence: 69%
“…The FT‐IR ranges (548.34 cm −1 –3286.85 cm −1 ) are most typically employed for functional group analysis in the production of AgNP from Spirulina platensis . silver nanoparticles produced by biosynthesis of Platensis Spirulina , [21] According to certain research, utilizing FT‐IR for AgNP functional group analysis reveals that the presence of numerous functional groups is responsible for the reduction of silver ions from salt solutions, such as AgNO 3 [22] . The FT‐IR spectrum of the extract showed prominent peaks at 3328, 2929 and 1600 cm −1 which are assigned to the OH, CH and C=O functional groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gram negative bacteria Acetobacter , Klebsiella , Proteus vulgaris , and Pseudomonas aeruginosa were cultivated on freshly produced nutrient broth media, [40] then inoculated on fresh petri plates with nutrient agar media. Test solution AgNP were added at concentration of 50 μl, 75 μl, and 100 μl, [41] to identify antibacterial activity of AgNP using agar well diffusion method [21] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticle effects on live species have received considerable attention in recent years [1, 2]. Many studies have shown that fungi [3, 4], bacteria [5, 6], and plants [7] are affected by various nanoparticles. Among living organisms, plants play a key role in food chains.…”
Section: Introductionmentioning
confidence: 99%